THE EVANGELICAL MIND IN A SECULAR AGE. (1st June 2015) - HEDSTROM, MATTHEW S.
Abstract : "Secular intellectuals have not been kind to the evangelical mind, " writes historian Molly Worthen in the opening sentence of Apostles of Reason: The Crisis of Authority in American Evangelicalism . Her history of evangelical thought after World War II is an extended effort to understand why. The answers, it turns out, entail not only specific and important critiques of evangelical theology, but also much larger trajectories in the modern intellectual history of the United States. Theology, after all, was once "the queen of the sciences, " the very foundation of all other intellectual labor, and remained central to American academic and intellectual culture well into the nineteenth century. Beginning at least with Thomas Jefferson in the United States, however, main currents in Protestant theology and elite intellectual life began their slow and steady divergence, a process that reached critical mass early in the twentieth century. Nowhere has this divergence been more evident, or created more crisis and drama, than among evangelicals.